Pengaruh Persepsi Atas Model Pembelajaran dan Motivasi Belajar Terhadap Keterampilan Menulis Artikel (Survey pada kelas XII Sekolah Menengah Kejuruan Swasta di Kota Tangerang Selatan Tahun Pelajaran 2022/2023) - Yanti, Nur Dwi; Sumaryoto, Sumaryoto; Suendarti, Mamik (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2023)
That the research aimed to investigate the relationship between perceptions of learning models, motivation to learn, and article writing skills among SMKS students in South Tangerang City. Here's a brief summary of your study's findings:1. There is a significant influence of both perceptions of learning models and motivation to learn on article writing skills among SMKS students in South Tangerang City. This is supported by the low p-value (Sig.) of 0.000, which is less than the common significance threshold of 0.05. The F-count of 17.165 and R value of 0.511 indicate that 51.1% of the variability in article writing skills can be explained by the combined influence of perceptions of learning models and motivation to learn. The remaining 48.9% of variability is attributed to unexamined factors.2. Perceptions of learning models have a significant influence on the article writing skills of SMKS students in South Tangerang City. The low significance level (Sig.) of 0.000, which is below the threshold of 0.05, and the provided t-count (t-value) of 0.907 indicate a statistically significant relationship between these variables.3. Motivation to learn also has a significant influence on article writing skills among SMKS students in South Tangerang City. The Sig. value of 0.000, which is less than 0.05, and the t-count (t-value) of 5.318 suggest a statistically significant relationship between motivation to learn and article writing skills. Overall, this study suggests that both perceptions of learning models and motivation to learn are important factors that influence article writing skills among SMKS students in South Tangerang City, and these findings are supported by statistically significant results.